Mekanisme Corporate Governance, Profitabilitas Dan Nilai Perusahaan Dengan Pengungkapan Corporate Social Responsibility Sebagai Pemoderasi - Mulyani, Dwi Septa; Uzliawati, Lia; Indriana, Ina (Politeknik Ganesha Medan, 2024)
This study aims to examine the effect of disclosure of Corporate Social Responsibility in moderating the relationship between corporate governance mechanisms and profitability with firm value in mining and energy companies. The corporate governance mechanism in this study is proxied by the board of commissioners and managerial ownership. The proxied of profitability on this study is Return On Equity. The research sample consists of 27 mining and energy companies listed on the Indonesia Stock Exchange for the 2017-2021 period. Data analysis was performed using Moderated Regression Analysis (MRA). The results showed that the board of commissionersand profitability have a positive influence on firm value., but managerial ownership have a negative influence to firm value. However, the existence of CSR disclosure can weaken the relationship between independent commissioners, managerial ownership and profitability with firm value.